The Role of Vasopressin V2 Receptor in Drug-Induced Hyponatremia - Kim, Sua; Jo, Chor Ho; Kim, Gheun-Ho (Frontiers in Physiology, 2021)
Hyponatremia is frequently encountered in clinical practice and usually induced by renal water retention. Many medications are considered to be among the various causes of hyponatremia, because they either stimulate the release of arginine vasopressin (AVP) or potentiate its action in the kidney. Antidepressants, anticonvulsants, antipsychotics, diuretics, and cytotoxic agents are the major causes of drug-induced hyponatremia. However, studies addressing the potential of these drugs to increase AVP release from the posterior pituitary gland or enhance urine concentration through intrarenal mechanisms are lacking. We previously showed that in the absence of AVP, sertraline, carbamazepine, haloperidol, and cyclophosphamide each increased vasopressin V2 receptor (V2R) mRNA and aquaporin-2 (AQP2) protein and mRNA expression in primary cultured inner medullary collecting duct cells. The upregulation of AQP2 was blocked by the V2R antagonist tolvaptan or protein kinase A (PKA) inhibitors. These findings led us to conclude that the nephrogenic syndrome of inappropriate antidiuresis (NSIAD) is the main mechanism of drug-induced hyponatremia. Previous studies have shown that the V2R has a role in chlorpropamide-induced hyponatremia. Several other agents, including metformin and statins, have been found to induce antidiuresis and AQP2 upregulation through various V2R-independent pathways in animal experiments, but are not associated with hyponatremia despite being frequently used clinically. In brief, drug-induced hyponatremia can be largely explained by AQP2 upregulation from V2R-cAMP-PKA signaling in the absence of AVP stimulation. This paper reviews the central and nephrogenic mechanisms of drug-induced hyponatremia and discusses the importance of the canonical pathway of AQP2 upregulation in drug-induced NSIAD.